Dukungan Rekan Kerja dalam Menghadapi Tekanan Kerja pada Staff Bagian Umum Dinas Kesehatan Provinsi Sumatera Selatan - Mutia Mawardah; Nia Oktaviani; Muhammad Ariandi; Liony Fitlady (Indo Publishing, 2026)
This study aims to describe the role of coworker support in dealing with work pressure experienced by the General Affairs Staf at the South Sumatra Provincial Health Office. Work pressure often arises due to high workloads, administrative demands, tight deadlines, and the need for high accuracy in completing tasks. This research used a descriptive quantitative approach involving five General Affairs staff members as respondents. Data were collected using questionnaires measuring coworker support and work pressure. The findings indicate that coworker support was generally in the high category, while work pressure was categorized as moderate. Emotional, instrumental, informational, and appraisal support contributed to reducing employees' work pressure. These findings support the Job Demand-Resources Model, which explains that coworker support acts as a job resource capable of reducing the negative impact of work demands. Therefore, fostering supportive relationships among coworkers is essential for maintaining employee well-being and improving organizational performance..